Studies in symbolic interaction. Vol. 28 - Denzin, Norman K.; Salvo, James (Elsevier JAI, 2005)
Volume 28 of "Studies in Symbolic Interaction" emphasizes new developments in interactional theory and practice, as well as examples of post-modern ethnography and performance texts focused on border crossings and border performances. The volume also presents essays honoring Carolyn Ellis' contributions to 'Symbolic Interaction and Communications', as well as the annual address in the "Peter M Hall Lecture" series.
Keywords: Symbolic interactionism.; Social, group or collective psychology.; Electronics & communications engineering.; Social Science -- Sociology -- General.; elektronické knihy; electronic books